DESIGN AND CHARACTERISATION OF TRANSDERMAL FILM OF GLICLAZIDE FOR THE TYPE-II DIABETES - Babu, V Rajesh (Asian Journal of Pharmaceutical Research and Development, 2018)
Oral drug delivery system has various drawbacks like poor bioavailability due to hepatic metabolism (first pass) and the tendency to produce rapid blood level spikes (both high and low), leading to a need for high and/or frequent dosing, which can be both cost prohibitive and inconvenient. In present study transdermal drug delivery of Gliclazide was developed to overcome the first pass metabolism and to reduce frequency of dosing compared to oral route. Matrix type of transdermal films were developed by using polymers Eudragit-S100, HPMCk4M and HPMCk15M.Transdermal films were prepared by employing solvent casting method. Propylene glycol was selected as permeation enhancer and plasticizer. Formulations were prepared with the varying concentrations polymers ranging from F1-F12, and all the formulations were evaluated for various physical parameters, invitro drug release studies by using dialysis membrane. Among all the formulations F5 formulation was found to be best and shown 94.7% drug release in 12 hours. For F5 formulation release kinetics were applied and it was observed that the formulation was following peppas mechanism of drug release. Drug excipient compatibility studies were carried out by using FTIR, and it was observed that they were no interactions.